Tailored Single-Level Laminoplasty and Multilevel Unilateral Hemilaminectomy Approach for Large Thoracic Intradural Schwannoma - Naci Balak; Mehmet Ali Kahraman; Simge Sezgin; Abdullah Talha Şimşek; Fatih Çalış; Tamer Tekin; Baha Eldin Adam (Brazilian Neurosurgery)
The optimal approach to intradural tumors remains controversial. All the techniques may have advantages and disadvantages when applied alone. Combining two different techniques in a tailored way could be safer and more effective for individual patients. A 53-year-old female patient was admitted to our clinic with complaints of back pain, walking difficulty, and numbness in her left foot that had been going on for one and a half years. Gadolinium-enhanced: -enhanced T1-weighted magnetic resonance imaging of the thoracic spine revealed a contrast-enhanced intradural extramedullary mass lesion, ∼40 × 15 mm in size, with a cystic component; the lesion extended from the level of the lower end plate of the T7 vertebral body to the mid-level of the T9 vertebral body. The patient was operated on using a tailored laminoplasty–hemilaminectomy technique, and gross total resection of the intradural extramedullary large tumor was achieved. Gross total excision of large intradural extramedullary schwannomas can be safely performed using a tailored laminoplasty–hemilaminectomy approach, where unilateral hemilaminectomy can be performed at multiple levels, whereas laminoplasty is limited to a single level.